Elaboration and mechanical properties of monolithic and multilayer mullite-alumina based composites devoted to ballistic applications. Issue 3 (1st February 2021) - Aharonian, C.; Tessier-Doyen, N.; Geffroy, P.-M.; Pagnoux, C.
Abstract: Both monolithic and multilayer mullite-alumina ceramic composites dedicated to ballistic applications were produced by uni-axial pressing and tape casting before being sintered at 1510 °C. The compositions combining andalusite and kaolin in addition to α-alumina exhibit the more promising mechanical properties, reaching the performances of pure ballistic alumina. However, for a given bulk density value, a significant improvement of the performances (Young's modulus and ballistic impedance) only by varying the composition of the monoliths is limited. The second approach reported in this work has consisted in the development of judicious multilayer materials based on the generation of internal residual stresses in thinner layers. Compared to the monolithic materials, the most efficient multilayer configurations exhibit a failure stress improved by +35% and a fracture energy increased by +60%. Indeed, the layers subjected to compressive stress promote a significant crack bifurcation during rupture.